Higher Education System in India: Are We Heading towards Right Direction? - Parvez, Mohammad; Shakir, Mohd (EDUCARE, 2013)
ABSTRACT: Education is power. Â It is empowerment. The dictums such as Aristotleâs âEducation is the best provision for old ageâ; Francis Baconâs âKnowledge is powerâ; Edward Bulwer-Lyttonâs âPen is mightier than swordâ; and many others are well known. They unveil the fact that education is a tool by which we can change our life as well as the life of others. Better the education in the society, more developed the society will be. In fact, education of a country in general and higher education in particular is very important for the growth and development of the society. India is now considered to be one of the most promising economies of the world. It is evident by the fact that Indiaâs Higher Education system is third largest in the world after China and United States of America (USA).Only quantity is not enough, quality is also very important; there are some issues and impediments which need immediate attention, like shortage of teachers, poor access to higher education. This paper is an attempt to discuss the issues in the higher education system of India, and also suggest some ways to cope up with these issues. We concluded that higher education system in India is not heading towards right direction; rather, it is heading towards wrong direction. If it wants to head towards right direction, then, the problems and issues should be taken seriously and solved on priority basis and then only our Indiaâs higher education system can come on the right track and consequently can compete with the worldâs best higher education system.KEY WORDS: Education, higher education, relevance, right direction, publication or multiplication, plagiarism, quality and quantity, and Indiaâs nation-state.Â Â About the Authors: Dr. Mohammad Parvez is an Associate Professor at the Department of Education AMU (Aligarh Muslim University), Aligarh 202002, UP (Uttar Pradesh), India; and Mohd Shakir is a Research Scholar at the Department of Education AMU, Aligarh, 202002, UP, India. The authors can be contacted via their e-mail at: mparvez9@yahoo.co.in and aligarhshakir@gmail.comHow to cite this article? Parvez, Mohammad & Mohd Shakir. (2013). âHigher Education System in India: Are We Heading towards Right Direction?â in EDUCARE: International Journal for Educational Studies, Vol.6(1) August, pp.35-42. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 9, 2013); Revised (July 20, 2013); and Published (August 17, 2013).Â Â